The Rationality and Price Effects of U.S. Department of Agriculture Forecasts of Oranges - BAUR, ROBERT F.; ORAZEM, PETER F. (Journal of Finance, 1994)
ABSTRACT This article examines the effect of public information on the orange juice market. We investigate the rationality, information content, and price effects of U.S. Department of Agriculture forecasts of the production of oranges. U.S. Department of Agriculture forecasts are found to be unbiased and efficient. The first forecast contains the most new information, and subsequent reports become valuable only when freezes occur. Significant price movements occur in response to announced production in both Florida and California. However, the majority of price variations cannot be explained by these movements in supply. We are always talking about overproduction. There would not be any overproduction if we could get these oranges at a decent price to the people who … could use them . The children need them ; they have so many vitamins . By keeping the price way up nobody can buy them and God knows, we get nothing for them . I sold my Valencias for 10 cents a box . I was offered 50 cents, and I thought I would hold out a little until I finally sold them for 10 cents . 1